A bioenergetic mechanism for amoeboid-like cell motility profiles tested in a microfluidic electrotaxis assay. Issue 11 (29th September 2017) - Peretz-Soroka, Hagit; Tirosh, Reuven; Hipolito, Jolly; Huebner, Erwin; Alexander, Murray; Fiege, Jason; Lin, Francis
Abstract : We explored a new bioenergetics model for amoeboid-like cell motility based on intracellular proton currents and cytoplasmic streaming (iPC-CS). Abstract : The amoeboid-like cell motility is known to be driven by the acidic enzymatic hydrolysis of ATP in the actin-myosin system. However, the electro-mechano-chemical coupling, whereby the free energy of ATP hydrolysis is transformed into the power of electrically polarized cell movement, is poorly understood. Previous experimental studies showed that actin filaments motion, cytoplasmic streaming, and muscle contraction can be reconstituted under actin-activated ATP hydrolysis by soluble non-filamentous myosin fragments. Thus, biological motility was demonstrated in the absence of a continuous protein network. These results lead to an integrative conceptual model for cell motility, which advocates an active role played by intracellular proton currents and cytoplasmic streaming (iPC-CS). In this model, we propose that protons and fluid currents develop intracellular electric polarization and pressure gradients, which generate an electro-hydrodynamic mode of amoeboid motion. Such energetic proton currents and active streaming are considered to be mainly driven by stereospecific ATP hydrolysis through myosin heads along oriented actin filaments. Key predictions of this model are supported by microscopy visualization and in-depth sub-population analysis of purified human neutrophils using a microfluidic electrotaxis assay. Three distinct phases in cell motility profiles, morphology, and cytoplasmic streaming in response to physiological ranges of chemoattractant stimulation and electric field application are revealed. Our results support an intrinsic electric dipole formation linked to different patterns of cytoplasmic streaming, which can be explained by the iPC-CS model. Collectively, this alternative biophysical mechanism of cell motility provides new insights into bioenergetics with relevance to potential new biomedical applications.